PEMBINAAN PEMBELAJARAN BAHASA INGGRIS BERBASIS KURIKULUM 2013 OLEH KEPALA SEKOLAH - Adhe Sisva Yulanda Afri Loren (UNIVERSITAS BENGKULU, 2015)
The general objective of this study was to describe the founding of implementation in leraning english based on curriculum 2013 by principal in Junior High School Number 02 Arga Makmur North Bengkulu. This study is qualitative descriptive study with qualitative naturalistic approach. Subjects in this study are the principal, the vice principal of curriculum, and teacher.Data collection techniques used in this study; observation, interviews, and documentation studies. Analysis of the data used 4 phases, namely data collection, data reduction, data presentation and conclusion or verification. The results showed that the founding of implementation in learningEnglish based on Curriculum 2013 by principal have done appropriate with the principal’s job and obigation as a principal.Keyword: founding, principal, curriculum 2013.